The Application of Socio-Cultural Pedagogical Approach in Teaching Popular Literature - Nestiani Hutami; Meria Zakiyah Alfisuma (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2022)
The trend of online learning during the Covid-19 pandemic has driven English Literature lecturers to come up with effective ways of teaching literature. Concerning this issue, this research aims to analyze how literature, especially popular literature, is taught online. Focusing on the socio-cultural pedagogic principles, the approach of teaching popular literature is examined using a qualitative descriptive approach. This study was conducted at English Literature Department, Adab and Humanity Faculty, UIN Sunan Ampel Surabaya, involving two popular literature lecturers. The data were obtained through interviews, observations, and documentation and analyzed using the interactive analysis method. It was found that the socio-cultural pedagogic principles were applied partially. (1) the principle of engagement was applied by warming-up questions, mind-mapping technique, mentioning adjectives, and watching movie trailers, (2) the principle of intelligibility was not applied because the lecturers explained the theory of genre and sub-genre characteristics before giving examples, and (3) the principle of participation was applied by delivering quizzes through various online platforms, like Google Classroom, Mentimeter, and Kahoot! and giving tasks which were uploaded in UIN Sunan Ampel’s e-learning system, SAILS ‘Sunan Ampel Integrated Learning Service’. The significance of these findings will contribute to the teaching and learning process of popular literature. Besides, the results will provide insight for popular literature lecturers to apply a better teaching approach.